Checklist and taxonomic changes for Central and South American Philonthina (Coleoptera: Staphylinidae) - Chani-Posse, Mariana; Newton, Alfred F.; Hansen, Aslak Kappel; Solodovnikov, Alexey (Zootaxa, 2018)
A checklist of all described species of Philonthina, a subtribe of the staphylinid tribe Staphylinini, known to occur in Central and South America (CASA) is presented. Included for each species, and for synonyms known from CASA, is a reference to the original description, type locality and type depository, and for each species the known distribution within and outside CASA. Type material was sought in the main European and American collections where it is deposited (BMNH, MNHUB, IRSNB and FMNH) and is summarized for all indigenous CASA species, with lectotypes designated for 16 names and confirmation of holotypes and prior designation of lectotypes when necessary. Based on recent phylogenetic work in Philonthina and our revision of types of CASA species of Philonthus Stephens, 1829 and Belonuchus Nordmann, 1837, some taxonomic changes are proposed. Thirty-one species of Philonthus are transferred to Belonuchus (16), Gabrius Stephens 1829 (14), and Bisnius Stephens 1829 (one) resulting in the following new combinations: B. abnormalis (Sharp 1885), B. celatus (Sharp 1885), B. corticalis (Sharp 1885), B. extremus (Sharp 1885), B. infimus (Sharp 1885), B. iteratus (Sharp 1887), B. latecinctus (Sharp 1885), B. lucilius (Sharp 1885), B. muticus (Sharp 1876), B. optatus (Sharp 1885), B. platypterus (Sharp 1885), B. rufiventris (Sharp 1887), B. rufocaudus (Sharp 1885), B. rufopygus (Sharp 1885), B. serraticornis (Sharp 1876), B. supernus (Herman 2001), G. approximans (Sharp 1885), G. armatipes (Sharp 1885), G. atricolor (Sharp 1885), G. championi (Sharp 1885), G. dampfi (Bernhauer 1929), G. elegans (Sharp 1885), G. forsterianus (Scheerpeltz 1960), G. misellus (Sharp 1885), G. nugax (Sharp 1885), G. ovaticeps (Sharp 1885), G. peruvianus (Bernhauer 1916), G. planulatus (Sharp 1885), G. rusticus (Sharp 1885), G. serpens (Sharp 1885) and Bi. subaeneipennis (Bernhauer 1916). Endeius nitidipennis Solier 1849 is transferred to Gabrius, resulting in the following new combination, G. nitidipennis (Solier 1849). Leptopeltus carchiensis Chani-Posse & Asenjo 2013 is proposed as junior synonym of Philonthus divisus Sharp 1891, which is transferred to Leptopeltus Bernhauer 1906 resulting in a new combination: Leptopeltus divisus (Sharp 1891). Belonuchus penetrans Silvestri 1946 is transferred to Pridonius Blackwelder 1952 as a new combination. Lectotypes are designated for Atopocentrum mirabile Bernhauer 1906, Philonthus armatipes Sharp 1885, Ph. atricolor Sharp 1885, Ph. championi Sharp 1885, Ph. misellus Sharp 1885, Ph. planulatus Sharp 1885, Ph. rusticus Sharp 1885, Ph. serpens Sharp 1885, Ph. abnormalis Sharp 1885, Ph. celatus Sharp 1885, Ph. infimus Sharp 1885, Ph. latecinctus Sharp 1885, Ph. muticus Sharp 1876, Ph. platypterus Sharp 1885, Ph. rufocaudus Sharp 1885 and Ph. rufopygus Sharp 1885. Of the 543 currently known species of Philonthina reported from CASA, at least 14 are believed to be adventive from elsewhere, 56 may occur naturally elsewhere, and 473 (87%) are evidently endemic to this region. Of the 31 genera represented by these described species, 20 (65%) are endemic to CASA. One genus, Gabronthus Tottenham 1955, is adventive. However, the actual philonthine fauna of CASA will undoubtedly be much larger, and the generic composition highly modified, when the fauna is fully explored and studied within a phylogenetical framework.